2013
DOI: 10.1583/13-4228.1
|View full text |Cite|
|
Sign up to set email alerts
|

A Proof-of-Concept In Vitro Study to Determine if EndoAnchors Can Reduce Gutter Size in Chimney Graft Configurations

Abstract: It is feasible to reduce gutters in CG configurations with the use of endoanchors in an in vitro juxtarenal aneurysm model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…Using in vitro models, Niepoth and colleagues showed that the use of EndoAnchors decreased the incidence of type 1a endoleaks associated with chimney graft stenting . They constructed silicone models that underwent Ch‐EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro models, Niepoth and colleagues showed that the use of EndoAnchors decreased the incidence of type 1a endoleaks associated with chimney graft stenting . They constructed silicone models that underwent Ch‐EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the risk of type IA endoleaks associated with the chimneygraft technique is directly proportional to the number of chimney grafts placed, we used an aortic fixation system to minimize these "gutter leaks." 9 The endovascular exclusion of a pararenal aneurysm is a complex procedure involving multiple techniques that, if executed precisely, can result in successful maintenance of visceral-artery perfusion via parallel stents, with minimal risk of morbidity and death. The chimney-graft technique is a viable alternative for high-risk patients who have a pararenal AAA and few treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, endoanchors have been in vitro evaluated in reducing the size of gutters in Ch-EVAR with promising results. 7,8 In the past, we successfully sealed a type Ia endoleak after chimney technique by using coil embolization and biological glue infusion. 9 However, multiple coil embolization sessions were required which resulted in an increased cost and endograft infection.…”
Section: Discussionmentioning
confidence: 99%